Association of Matrix Metalloproteinase 9 (MMP-9) Polymorphisms with Asthma Risk: A Meta-Analysis. (25th February 2019) - Zou, Fenfang; Zhang, Jianpeng; Xiang, Guoan; Jiao, Hongbin; Gao, Hongmei
Abstract : Published data on the association between MMP-9 polymorphisms (−1562 C > T, rs3918242; Gln279Arg, rs17576 Arg668Gln, rs17577) and asthma susceptibility are inconclusive. To derive a more precise estimation of this association, a meta-analysis was performed. A literature search was conducted in PubMed, Web of Science, EMBASE, Wanfang, and China National Knowledge Infrastructure (CNKI) databases to identify eligible studies. The pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were used to calculate the strength of association. Sensitivity analysis was performed to evaluate the influence of individual studies on the overall effect estimates, and funnel plots and Egger's test were inspected for indication of publication bias. Seven studies with 1592 asthma patients and 1987 controls were finally identified. Overall, we found no significant association between −1562 C > T, rs3918242 polymorphism, and asthma susceptibility in any of the genetic model comparisons. After categorizing studies into different subgroups on the basis of ethnicity and age, there is still no significant association. For the Gln279Arg, rs17576 polymorphism, there seems to be a significant association in the allelic genetic model in regard to theP value (OR = 1.11, 95% CI = 1.00–1.22, I 2 = 0%, P Z = 0.044 ); however, the value of lower 95% CI is 1.0. For the Arg668Gln, rs17577 polymorphism, a high significant association was observed in the dominant model comparison (OR = 1.65, 95% CI = 1.28–2.11, I 2 = 22.50%, P Z = 0 ), recessive model comparison (OR = 2.40, 95% CI = 1.23–4.72, I 2 = 0%, P Z = 0.011 ), homozygote genotype comparison (OR = 2.69, 95% CI = 1.36–5.33, I 2 = 0%, P Z = 0.004 ), and allelic genetic model (OR = 1.59, 95% CI = 1.29–1.97, I 2 = 36.9%, P Z = 0 ). Sensitivity analysis demonstrated the stability of our results, and publication bias was not evident. The present meta-analysis suggests that MMP-9 Arg668Gln, rs17577 polymorphism may be the risk factor for asthma susceptibility.